Kekerasan Dalam Rumah Tangga Sebagai Alasan Perceraiaan (Analisis Putusan Nomor 737/Pdt.G/2021/PA.TPI Perspektif Saddu Adz-Dzari’ah) - Rizki Amar; Isyaq Maulidan; M. Rafli Kurniawan (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2024)
This paper aims to examine the decision of the Religious Court No. 737/Pdt.G/2021/Pa.Tpi regarding the case of divorce due to domestic violence from the perspective of saddu adz-dzari'ah. This paper focuses on the reasoning of the panel of judges who directed their consideration to article 19 letter (f) of PP No. 9 of 1975 'jo article 116 (f) KHI and saw the relevance of the decision to the saddu adz-dzari'ah theory. This research uses a juridical-empirical approach and makes saddu adz-dzari'ah as an analytical. From this study, it is known that the panel of judges interpreted the act of domestic violence as a result of disputes and quarrels, therefore the Panel of Judges in its legal considerations applied Article 19 letter (f) PP No. 9 of 1975 jo. Article 116 letter (f) KHI. The granting of the divorce suit follows the theory of saddu adz-dzari'ah where marriage which should be a wasilah to happiness, the benefit of husband and wife does not materialise. On the contrary, the marriage becomes a wasilah to kemafsadatan (disputes and quarrels) and prohibited behaviour (domestic violence).